Halal Animal Slaughter in the Era of Industrialization and Global Trade: Between Sharia Compliance and Food Safety Standards - Abdullah (IQRAR: Jurnal Akuntansi, Manajemen & Ekonomi Syariah, 2025)
The halal integrity of animal slaughter has become a critical issue in the era of industrialization and global trade, particularly as traditional practices confront mechanization, food safety standards, and international supply chains. This study aims to analyze the balance between Sharia compliance and food safety standards within the context of halal slaughter. A qualitative literature review approach was employed by examining scholarly articles, books, and international documents from reputable databases. The findings reveal that industrialization presents challenges to ritual authenticity, halal certification harmonization, and consumer demands for transparency and animal welfare. The implication is that halal slaughter can be positioned not only as a religious obligation but also as a framework for ethical and sustainable food governance in global markets